(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article studies the religious traditions and ceremonies of the Jews of Bukhara, one of the oldest Jewish communities of Central Asia. On the basis of field research and a wide range of Jewish, Russian, Turkish, and Western scholarly sources, it examines the Sabbath and daily prayers, the annual festivals, and the life-cycle ceremonies – circumcision (brit milah), the naming of children, bar mitzvah, marriage (kiddushin and ketubah), and the rites surrounding death – showing how the Bukharan Jews preserved normative Jewish practice while developing local features of their own.